Growth and phosphorus uptake by cassava in P-deficient soil in response to mycorrhizal inoculation - Lucas Guilherme Cavallari; Adalton Mazetti Fernandes; Lydia Helena da Silva de Oliveira Mota; Hugo Mota Ferreira Leite; Valkíria Luísa Borsa Piroli (Revista Brasileira de Ciência do Solo, 2021)
ABSTRACT Phosphorus (P) is one of the most difficult nutrients for plants to acquire because of its low content in the soil solution. Cassava (Manihot esculenta Crantz) has a thick and sparse absorbent root system; therefore, it is dependent on its association with arbuscular mycorrhizal fungi (AMF) for P acquisition from the soil. Thus, inoculation of cassava with AMF can improve the development of this root crop. This study evaluated the effects of soil disinfection (disinfected vs. natural) and the spore rates of Rhizophagus clarus inoculation (0, 50, 100 and 200 spores per plant) in greenhouse conditions on the initial growth, yield, P acquisition, and P use efficiency of cassava, as well as to evaluate the contribution of the native AMF to P acquisition from the soil. For cassava production in P-deficient soil, inoculation with Rhizophagus clarus significantly increased cassava growth, P uptake, and storage root yield only when the soil was disinfected. When the soil is not disinfected, native AMF contributes up to 86 % of the P taken up by cassava. However, high spore rates of Rhizophagus clarus in natural soil cause detrimental consequences for native AMF by reducing the colonization of the absorbent roots. Therefore, for cassava grown in natural soil under greenhouse conditions, a rate of 50 spores per plant of Rhizophagus clarus is sufficient to promote a 14.5 % increase in the yield of fresh storage roots. A management strategy that favors the native AMF multiplication in the soil is a potential strategy to improve P uptake and yield of cassava in P-deficient soils.